G Gejala Menopause pada Wanita Premenopause - Fruitasari, MK. Fitriani (Journal of Nursing Invention, 2024)
Background: Menopause for a woman is a phase that every woman will reach at the age of 40 to 50 years. It is said that she has reached menopause if her menstrual cycle has stopped for at least 12 months. Before menopause, there is a period of preparation for menopause called the pre-menopause period. This study aims to describe the symptoms of menopause in premenopausal women. Method: Quantitative descriptive research design with a sample size of 96 (20% premenopausal women) from a total population of 482 women. Results: The results of this study illustrate that hot flush symptoms were felt by 10.5% of women, night sweat symptoms were felt by 36.5% of women. Symptoms of fatigue and sleep disturbances were felt by 50% and 52.1% of women on a mild scale and 3.2% on a medium scale. Symptoms of memory loss were felt by 46.9% of women. Symptoms of anxiety on a mild scale were felt by 16.7% of women. 8.3% of women felt similar symptoms on a mild scale. Symptoms of mild depression were only felt by 1.04% of women. Conclusion: Premenopausal women have begun to experience menopausal symptoms on a mild scale, such as hot flashes, night sweats, fatigue, sleep disturbances, memory loss, anxiety, isolation and depression. There are even some premenopausal women who already experience moderate symptoms of menopause. disturbances, memory loss, anxiety, isolation and depression.